HIV treatment outcomes among people who acquired HIV via injecting drug use in the Asia‐Pacific region: a longitudinal cohort study. Issue 5 (21st May 2021) - Han, Win Min; Jiamsakul, Awachana; Salleh, Nur Afiqah Mohd; Choi, Jun Yong; Huy, Bui Vu; Yunihastuti, Evy; Do, Cuong Duy; Merati, Tuti P; Gani, Yasmin M; Kiertiburanakul, Sasisopin; Zhang, Fujie; Chan, Yu‐Jiun; et al.
Abstract: INTRODUCTION: Data on HIV treatment outcomes in people who inject drugs (PWID) in the Asia‐Pacific are sparse despite the high burden of drug use. We assessed immunological and virological responses, AIDS‐defining events and mortality among PWID receiving antiretroviral therapy (ART). METHODS: We investigated HIV treatment outcomes among people who acquired HIV via injecting drug use in the TREAT Asia HIV Observational Database (TAHOD) between January 2003 and March 2019. Trends in CD4 count and viral suppression (VS, HIV viral load <1000 copies/mL) were assessed. Factors associated with mean CD4 changes were analysed using repeated measures linear regression, and combined AIDS event and mortality were analysed using survival analysis. RESULTS: Of 622 PWID from 12 countries in the Asia‐Pacific, 93% were male and the median age at ART initiation was 31 years (IQR, 28 to 34). The median pre‐ART CD4 count was 71 cells/µL. CD4 counts increased over time, with a mean difference of 401 (95% CI, 372 to 457) cells/µL at year‐10 (n = 78). Higher follow‐up HIV viral load and pre‐ART CD4 counts were associated with smaller increases in CD4 counts. Among 361 PWID with ≥1 viral load after six months on ART, proportions with VS were 82%, 88% and 93% at 2‐, 5‐ and 10‐years following ART initiation. There were 52 new AIDS‐defining events and 50 deaths during 3347 person‐years of follow‐up (PYS) (incidence 3.05/100 PYS, 95% CI, 2.51 to 3.70). Previous AIDS or TB diagnosis, lower current CD4 count and adherence <95% were associated with combined new AIDS‐defining event and death. CONCLUSIONS: Despite improved outcomes over time, our findings highlight the need for rapid ART initiation and adherence support among PWID within Asian settings.